Communicating flood risk: Looking back and forward at traditional and social media outlets - Feldman, David; Contreras, Santina; Karlin, Beth; Basolo, Victoria; Matthew, Richard; Sanders, Brett; Houston, Douglas; Cheung, Wing; Goodrich, Kristen; Reyes, Abigail; Serrano, Kimberly; Schubert, Jochen; et al. (International Journal of Disaster Risk Reduction, 2016)
The communication of information about natural hazard risks to the public is a difficult task for decision makers. Research suggests that newer forms of technology present useful options for building disaster resilience. However, how effectively these newer forms of media can be used to inform populations of the potential hazard risks in their community remains unclear. This research uses primary data from an in-person survey of 164 residents of Newport Beach, California during the spring of 2014 to ascertain the current and preferred mechanisms through which individuals receive information on flood risks in their community. Factor analysis of survey data identified two predominant routes of dissemination for risk information: older traditional media and newer social media sources. A logistic regression model was specified to identify predictors for choosing a particular communication route. This analysis revealed that age is the central factor in predicting the sources people use to receive risk information. We follow the analysis by discussing this finding and its policy implications.

Accounting for three sources of uncertainty in ensemble hydrological forecasting - Thiboult, Antoine; Anctil, François; Boucher, Marie-Amélie (Hydrology and Earth System Sciences, 2016)
Abstract. Seeking more accuracy and reliability, the hydrometeorological community has developed several tools to decipher the different sources of uncertainty in relevant modeling processes. Among them, the ensemble Kalman filter (EnKF), multimodel approaches and meteorological ensemble forecasting proved to have the capability to improve upon deterministic hydrological forecast. This study aims to untangle the sources of uncertainty by studying the combination of these tools and assessing their respective contribution to the overall forecast quality. Each of these components is able to capture a certain aspect of the total uncertainty and improve the forecast at different stages in the forecasting process by using different means. Their combination outperforms any of the tools used solely. The EnKF is shown to contribute largely to the ensemble accuracy and dispersion, indicating that the initial conditions uncertainty is dominant. However, it fails to maintain the required dispersion throughout the entire forecast horizon and needs to be supported by a multimodel approach to take into account structural uncertainty. Moreover, the multimodel approach contributes to improving the general forecasting performance and prevents this performance from falling into the model selection pitfall since models differ strongly in their ability. Finally, the use of probabilistic meteorological forcing was found to contribute mostly to long lead time reliability. Particular attention needs to be paid to the combination of the tools, especially in the EnKF tuning to avoid overlapping in error deciphering.
Keywords: Ouvrage_Collectif_Numéro1

Gravel-bed river floodplains are the ecological nexus of glaciated mountain landscapes - Hauer, F. Richard; Locke, Harvey; Dreitz, Victoria J.; Hebblewhite, Mark; Lowe, Winsor H.; Muhlfeld, Clint C.; Nelson, Cara R.; Proctor, Michael F.; Rood, Stewart B. (Science Advances, 2016)
Gravel-bed rivers are disproportionately important to regional biodiversity, species interactions, connectivity, and conservation. , Gravel-bed river floodplains in mountain landscapes disproportionately concentrate diverse habitats, nutrient cycling, productivity of biota, and species interactions. Although stream ecologists know that river channel and floodplain habitats used by aquatic organisms are maintained by hydrologic regimes that mobilize gravel-bed sediments, terrestrial ecologists have largely been unaware of the importance of floodplain structures and processes to the life requirements of a wide variety of species. We provide insight into gravel-bed rivers as the ecological nexus of glaciated mountain landscapes. We show why gravel-bed river floodplains are the primary arena where interactions take place among aquatic, avian, and terrestrial species from microbes to grizzly bears and provide essential connectivity as corridors for movement for both aquatic and terrestrial species. Paradoxically, gravel-bed river floodplains are also disproportionately unprotected where human developments are concentrated. Structural modifications to floodplains such as roads, railways, and housing and hydrologic-altering hydroelectric or water storage dams have severe impacts to floodplain habitat diversity and productivity, restrict local and regional connectivity, and reduce the resilience of both aquatic and terrestrial species, including adaptation to climate change. To be effective, conservation efforts in glaciated mountain landscapes intended to benefit the widest variety of organisms need a paradigm shift that has gravel-bed rivers and their floodplains as the central focus and that prioritizes the maintenance or restoration of the intact structure and processes of these critically important systems throughout their length and breadth.
Keywords: Ouvrage_Collectif_Numéro1

Guide to identifying alert thresholds for heat waves in Canada based on evidence - Gachon, P.; Bussières, Louise; Gosselin, P.; Raphoz, M.; Bustinza, R.; Martin, Philippe H.; Dueymes, G.; Gosselin, Denis; Labrecque, Sylvain; Jeffers, S.; Yagouti, Abderrahmane (2016)
Among natural-disaster risks, heat waves are responsible for a large number of deaths, diseases and economic losses around the world. As they will increase in severity, duration and frequency over the decades to come within the context of climate change, these extreme events constitute a genuine danger to human health, and heat-warning systems are strongly recommended by public health authorities to reduce this risk of diseases and of excessive mortality and morbidity. Thus, evidence-based public alerting criteria are needed to reduce impacts on human health before and during persistent hot weather conditions. The goal of this guide is to identify alert thresholds for heat waves in Canada based on evidence, and to propose an approach for better defining heat waves in the Canadian context in order to reduce the risks to human health and contribute to the well-being of Canadians. This guide is the result of the collaboration among various research and public institutions working on: 1) meteorological and climate aspects, i.e. the Meteorological Service of Canada (MSC, Environment and Climate Change Canada), and the ESCER centre at the Universite du Quebec a Montreal, and 2) public health, i.e. Health Canada and the Institut National de Sante Publique du Quebec.
Keywords: Gachon_Philippe

Identification of changes in floods and flood regimes in Canada using a peaks over threshold approach - Burn, Donald H.; Whitfield, Paul H.; Sharif, Mohammed (Hydrological Processes, 2016)
Abstract Recent flood events in Canada have led to speculation that changes in flood behaviour are occurring; these changes have often been attributed to climate change. This paper examines flood data for a collection of 132 gauging stations in Canada. All of these watersheds are part of the Canadian Reference Hydrometric Basin Network (RHBN), a group of gauging stations specifically assembled to assist in the identification of the impacts of climate change. The RHBN stations are considered to have good quality data and were screened to avoid the influences of regulation, diversions, or land use change. Daily flow data for each watershed are used to derive a peaks over threshold (POT) dataset. Several measures of flood behaviour are examined based on the POT data, which afford a more in‐depth analysis of flood behaviour than can be obtained using annual maxima data. Analysis is conducted for four time periods ranging from 50 to 80 years in duration; the latter period results in a much smaller number of watersheds that have data for the period. The changes in flood responses of the watersheds are summarized by grouping the watersheds by size (small, medium, and large) and also by hydrologic regime (nival, mixed, and pluvial). The results provide important insights into the nature of the changes that are occurring in flood regimes of Canadian rivers, which include more flood exceedances, reduced maximum flood exceedance magnitudes for snowmelt events, and earlier flood events. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

La résilience des personnes âgées à la suite de leur exposition à un sinistre - Maltais, Danielle; Gauthier, Simon (2016)
Keywords: Ouvrage_Collectif_Numéro1

Supreme: An Integrated Heat Health Warning System for Québec - Gosselin, P.; Bustinza, R.; Sharon, J.; Gachon, P.; Bussieres, L.; Gosselin, D.; Martin, P.; Labrecque, S. (Climate Services for Health: Improving public health decision-making in a new climate. Chapter 5: Co-development and delivery of health-tailored climate products and services, Case Study 5K, 2016)
Keywords: Gachon_Philippe

Health effects of flooding in Canada: A 2015 review and description of gaps in research - Burton, Hilary; Rabito, Felicia; Danielson, Lisa; Takaro, Tim (Revue canadienne des ressources hydriques 41 : 1-2, 2016)

Exposure to flood hazards in Miami and Houston: are Hispanic immigrants at greater risk than other social groups? - Maldonado, Alejandra; Collins, Timothy W.; Grineski, Sara E.; Chakraborty, Jayajit (International Journal of Environmental Research and Public Health, 2016)
Although numerous studies have been conducted on the vulnerability of marginalized groups in the environmental justice (EJ) and hazards fields, analysts have tended to lump people together in broad racial/ethnic categories without regard for substantial within-group heterogeneity. This paper addresses that limitation by examining whether Hispanic immigrants are disproportionately exposed to risks from flood hazards relative to other racial/ethnic groups (including US-born Hispanics), adjusting for relevant covariates. Survey data were collected for 1283 adult householders in the Houston and Miami Metropolitan Statistical Areas (MSAs) and flood risk was estimated using their residential presence/absence within federally-designated 100-year flood zones. Generalized estimating equations (GEE) with binary logistic specifications that adjust for county-level clustering were used to analyze (separately) and compare the Houston (N = 546) and Miami (N = 560) MSAs in order to clarify determinants of household exposure to flood risk. GEE results in Houston indicate that Hispanic immigrants have the greatest likelihood, and non-Hispanic Whites the least likelihood, of residing in a 100-year flood zone. Miami GEE results contrastingly reveal that non-Hispanic Whites have a significantly greater likelihood of residing in a flood zone when compared to Hispanic immigrants. These divergent results suggest that human-flood hazard relationships have been structured differently between the two MSAs, possibly due to the contrasting role that water-based amenities have played in urbanization within the two study areas. Future EJ research and practice should differentiate between Hispanic subgroups based on nativity status and attend to contextual factors influencing environmental risk disparities.
MAG ID: 2480285246